(untitled) (Journal of the College of Basic Education, 2026)
This research lies in identifying the relationship between changes in the amount of oil production and prices and their direct and indirect impact on the economic and political crisis in Iraq that show the geographical distribution of the southern and northern oil fields of oil production and its impact on regional development and economic imbalance in the governorates of Iraq for the period (2003-2020) and studying them cartographically, as the Iraqi state depends heavily on oil revenues, where oil constitutes more than 90% of the general budget. Since 2003, Iraq has witnessed sharp fluctuations in oil prices, which has clearly reflected on the economic and political performance, which caused crises in financing projects and services, as well as led to the deterioration of infrastructure and the escalation of unemployment and poverty rates, especially in the regions